'I'm praying for a miracle': characteristics of spiritual statements in paediatric intensive care unit care conferences. Issue Volume 12:Issue e5(2022) (27th August 2020) - Gradick, Katie; October, Tessie; Pascoe, David; Fleming, Jeff; Moore, Dominic
Abstract : Context: Supporting spiritual needs is a well-established aspect of palliative care, but no data exist regarding how physicians engage with patients and families around spirituality during care conferences in paediatric intensive care units (PICU). Objectives: To assess the frequency and characteristics of family and physician spiritual statements in PICU care conferences. Methods: We performed qualitative analysis of 71 transcripts from PICU conferences, audio-recorded at an urban, quaternary medical centre. Transcripts were derived from a single-centre, cross-sectional, qualitative study. Results: We identified spiritual language in 46% (33/71) of PICU care conferences. Spiritual statements were divided relatively evenly between family member (51%, 67/131) and physician statements (49%, 64/131). Physician responses to families' spiritual statements were coded as supportive (46%, 31/67), deferred (30%, 20/67), indifferent (24%, 16/67) or exploratory (0/67). Conclusions: In this single-centre PICU, spiritual statements were present 46% of the time during high stakes decision-making conferences, but there was little evidence of spiritual care best practices, such as offering chaplain support and performing open-ended spiritual assessments. PICU clinicians should expect spiritual statements in care conferences and be prepared to respond.